BIMBINGAN DAN KONSELING ISLAM DALAM MENANGANI MASALAH KELUARGA MELALUI ACARA BENGKEL KELUARGA SAKINAH DI TV9 SURABAYA (Jurnal Bimbingan dan Konseling Islam, 2013)
This study uses content analysis approach with the type of descriptive research that the researcher wants to obtain information and content communications submitted by KH. Sumarkhan in addressing family issues in the event TV9 Surabaya Sakinah Family Workshop in Guidance and Counseling Islamic perspective. Then the researchers will describe or depict in fact correspond to reality in the event. The results showed that: Sakinah Family Workshop Event is the event that presents the material or discussion of family problems which aired live on TV9 station in the city of Surabaya. In the event there is Islamic guidance and counseling services, where KH. Sumarkhan as an Islamic counselor to help resolve family problems experienced by the audience in attendance at TV9 studio and viewers at home who witnessed the event. In overcoming family problems, KH. Sumarkhan functioning optimally religious values. Foundation (foundation or major foundation) used KH. Sumarkhan in the implementation of Guidance and Counselling Islam is Al - Quran and Al - Hadith.Keywords : Contents Analysis , Guidance and Counseling Islam